Effects of fines on critical hydraulic gradient of soils at optimum moisture content - Janarthanan, B. (My University, 2013)
Critical hydraulic gradient is an essential parameter for determining the factor of safety against piping failure of earthen dams, excavations, etc. Theoretically, the critical hydraulic gradient of a soil is taken as a function of the saturated unit weight of soil. The occurrence and development of piping is a very complex process due to complicated interactions between water and soil. It was observed that fines content and plasticity characteristics of soil affect the initiation of piping of soils. In addition, the above properties affect the roof supporting capabilities of soil, which is an essential criterion for propagation of piping. This paper is based on a study of the effect of fines content of soil on the initiation of piping at optimum moisture content. Soil with particle size of 0.075 to 2 mm and fine sand with particle size of less than 0.075 mm were mixed at different mass percentages. By performing the proctor compaction test optimum moisture content was found. Sample was prepared at the optimum moisture content and placed in mould and immersed into stable water slowly to get saturated sample. Series of permeability tests were performed to measure the critical hydraulic gradient. The critical hydraulic gradient was greater than the theoretical critical hydraulic gradient and increased with the increment of fine percentage.
Keywords: Critical hydraulic gradient; Piping; Plasticity